UPAYA PENINGKATAN PENGETAHUAN PADA IBU GAMPONG MEUNASAH INTAN KECAMATAN KUTA BARO KABUPATEN ACEH BESAR DALAM PENCEGAHAN STUNTING - Anggraini, Yayu; Zahara, Hafni; Lensoni; Kala, Pasyamei Rembune; Raisah, Putri; Murni; Saifuddin; Andriaty, Syarifah Nora (Transpublika Publisher, 2022)
The prevalence of stunting in Aceh Province is 44.6% on a national scale, while the prevalence in Banda Aceh is 38.8%. Given the cause of the incident, it is vital to emphasize that as well. The objective of this study was to explore the relationship between exclusive breastfeeding, complementary feeding, immunization status, and family characteristics with the incidence of stunting in infants. A total of 96 samples were collected from the areas of Puskesmas Banda Raya, Batoh, and Meuraxa as part of this quantitative study employing a Case-Control Study design. The analysis of data was performed univariately and bivariately using the Chi-square test with a 95% confidence interval, and multivariately (logistic regression). The results showed that the incidence of stunting in infants was caused by low family income (p = 0.026; OR = 3.1), non-exclusive breastfeeding (p = 0.002; OR = 4.2), inadequate complementary feeding (p = 0.007); OR = 3.4), and incomplete immunization (p = 0.040; OR = 3.5). The results of the multivariate analysis revealed that non-exclusive breastfeeding was a significant contributor to infant stunting in the Banda Aceh region, with an odds ratio (OR) of 4.9. Accordingly, stunting in children is linked to a lower family income, breastfeeding that is not exclusive, inadequate complementary nutrition, and insufficient immunization. In contrast, non-exclusive breastfeeding is the major contributing factor for children with stunting.